A comprehensive pan-cancer analysis unveiling the oncogenic effect of plant homeodomain finger protein 14 (PHF14) in human tumors - Cao, Zhiyou; Zhan, Haibo; Wu, Weiwei; Kuang, Zhihui; Mo, Fengbo; Liu, Xuqiang; Dai, Min (Frontiers in Genetics, 2023)
The plant homeodomain (PHD) finger refers to a protein motif that plays a key role in the recognition and translation of histone modification marks by promoting gene transcriptional activation and silencing. As an important member of the PHD family, the plant homeodomain finger protein 14 (PHF14) affects the biological behavior of cells as a regulatory factor. Several emerging studies have demonstrated that PHF14 expression is closely associated with the development of some cancers, but there is still no feasible pan-cancer analysis. Based on existing datasets from the Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO), we performed a systematic analysis of the oncogenic role of the PHF14 gene in 33 human cancers. The expression level of PHF14 was significantly different between different types of tumors and adjacent normal tissues, and the expression or genetic alteration of PHF14 gene was closely related to the prognosis of most cancer patients. Levels of cancer-associated fibroblasts (CAFs) infiltration in various cancer types were also observed to correlate with PHF14 expression. In some tumors, PFH14 may play a role in tumor immunity by regulating the expression levels of immune checkpoint genes. In addition, the results of enrichment analysis showed that the main biological activities of PHF14 were related to various signaling pathways or chromatin complex effects. In conclusion, our pan-cancer research shows that the expression level of PHF14 is closely related to the carcinogenesis and prognosis of certain tumors, which needs to be further verified by more experiments and more in-depth mechanism exploration.